Case Report: Kearns Sayre Syndrome Complicated With Postpartum Cardiac Failure - Han, Caixia; Jia, Zongyang; Zhao, Guangcai; Chen, Wenhui; Hu, Yue; Liu, Haiying (Frontiers in Medicine, 2022)
Kearns Sayre Syndrome(KSS) is a rare form of the mitochondrial disease characterized by a primary dysfunction of the mitochondrial respiratory chain. Cardiac involvement is a poor prognostic factor of KSS. Pregnancy and delivery in KSS with cardiac involvement is uncommon and strategies about the supervision and management for this group remain not clear. Herein, we report and discuss pregnancy and delivery complicated with acute cardiopulmonary failure in a woman with KSS.